Refugee protection and responsibility sharing in Latin America: solidarity programmes and the Mexico Plan of Action. Issue 2 (17th February 2016) - Barichello, Stefania Eugenia
Abstract : The aim of this article is to analyse the three solidarity programmes in the Mexico Plan of Action (MPA) – the responsibility sharing programme for regional resettlement, the integration of refugees into safe communities, and the development of border regions. The MPA is a step forward in strengthening the protection of human rights and the affirmation of the universality of human dignity. The MPA's objectives and programmes promote responsibility both at the regional level, through the notions of international solidarity and shared responsibility, and at the international level, as cooperation at a regional level could encourage similar initiatives in other regions.